АНАЛІЗ КОЛИВНОЇ СТАТИЧНОЇ СТІЙКОСТІ ОЕС УКРАЇНИ З ВИКОРИСТАННЯМ ГАРМОНІЧНИХ ФУНКЦІЙ ЗМІННОЇ АМПЛІТУДИ - Авраменко, В.М.; Мартинюк, О.В.; Гурєєва, Т.М. (Інститут електродинаміки НАН України, Київ, 2017)
The purpose of this work is to investigate the approximation method using a damped harmonic functions (DHF) for power flows on the line in the section of the IPS of Ukraine, to estimate the level of steady state stability in crosssection. The research method is simulation of free oscillations by the calculation of electromechanical transient process after a small disturbance. On the basis of calculations of transients after a small disturbance of the real IPS mode, the approximation functions for modes with different levels of stability are obtained. It is shown the connection of the safety factor, or the excess of the limit flow with the dynamics of the approximation function parameters. References 7, table 1, figures 7.